1996
DOI: 10.1002/j.1460-2075.1996.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

The IVS6 segment of the L-type calcium channel is critical for the action of dihydropyridines and phenylalkylamines.

Abstract: The current through the L‐type calcium channel is inhibited and stimulated by distinct dihydropyridines at very low concentrations. The molecular determinants for the high affinity block and stimulation were investigated using chimeras between the class C and E calcium channels. Mutation of three amino acids in the last putative transmembrane segment (IVS6) of the alpha1C subunit decreased the affinity for (+)isradipine 100‐fold without significantly affecting the basic properties of the expressed channel. Mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
107
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 25 publications
15
107
0
Order By: Relevance
“…Kass and colleagues found that the DHP receptor site lies within the lipid bilayer approximately 11-14 Å from the extracellular surface of the membrane (3). These conclusions are consistent with mutagenic studies where individual amino acid residues located on transmembrane segments IIIS5, IIIS6 and IVS6 were found to be critical for DHP binding and activity (4)(5)(6)(7)(8).…”
supporting
confidence: 90%
“…Kass and colleagues found that the DHP receptor site lies within the lipid bilayer approximately 11-14 Å from the extracellular surface of the membrane (3). These conclusions are consistent with mutagenic studies where individual amino acid residues located on transmembrane segments IIIS5, IIIS6 and IVS6 were found to be critical for DHP binding and activity (4)(5)(6)(7)(8).…”
supporting
confidence: 90%
“…This property was responsible for the inhibition of cardiac contraction by 1 M nisoldipine, since at depolarized membrane potentials which are necessary for channel opening the affinity for nisoldipine increased significantly. The affinity of the Ca v 1.2 channel for DHPs is lowered 100-fold by mutation of Tyr-1485, Met-1486, and Ile-1493 in the IVS6 segment (39) and is lost upon mutation of Thr-1061 in the IIIS5 segment (see Refs. 3,5,and 20).…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis was performed using the QuikChangeXL kit (Stratagene) according to the manufacturer's instructions. This DHP-insensitive mutant contained mutations at the critical residues Thr1066 in IIIS5 [4,14,15], as well as Phe 1463, Met1464, and Iso1471 in IVS6 [3][4][5]. These mutations have previously been shown to decrease the affinity of α 1c for dihydropyridines by over 100-fold, without significant effects on the biophysical properties of the channel [3].…”
Section: Experimental Procedures α 1c-d-plasmid Preparationmentioning
confidence: 99%
“…The largest component is the pore-forming α 1 subunit (∼220 kDa), the critical determinant of most functional properties of the channel, including voltage-dependent gating, Ca 2+ permeability, Ca 2+ -dependent inactivation [1,2], and inhibition by the three principal classes of Ca 2+ channel antagonists [3][4][5].…”
Section: Introductionmentioning
confidence: 99%